Pengembangan Sistem Rekomendasi Rute Paling Optimum Dengan Algoritme Voronoi Continuous K Nearest Neighbor (VCKNN), Progressive Incremental Network Expansion (PINE), Voronoi-Based Network Nearest Neighbor (VN3), Berbasis Webgis - Fajar Krisna Wicaksono; Fatwa Ramdhani; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In daily life, people in Malang often travel from one place to another by considering the efficiency of travel time. Lowokwaru is one of the densely populated sub-districts in Malang City. Therefore, traffic jam often occurs frequently at certain time. Path searching is one of the solutions in handling traffic jam at certain time in Malang. This research uses the Voronoi-Based Continuous K Nearest Neighbor (VCKNN), Progressive Incremental Network Expansion (PINE), Voronoi-Based Network Nearest Neighbor (VN3) algorithms. Every algorithm has different calculation steps and data models, it affects the computing time of every algorithm that affects the response time of the system. In the VCKNN, PINE and VN3 algorithms, the route searching process is divided into two stages, the first stage is searching for the voronoi neighbor to filter the data based on the voronoi polygon, after that, it searches the route on the voronoi polygon. This research was conducted to find out the response time, the number of passed node and the relationship between response time and the number of passed node, so the most efficient algorithm in the problem of route searching was known. From this research it was known that the algorithm with the fastest response time was VCKNN algorithm with 0.071 seconds response time and the algorithm with the lowest number of passed node was PINE algorithm with the number of nodes passed by 17 nodes. From the results of the research, the most efficient algorithm in determining the optimum route was the VCKNN algorithm.